“Kind regards”: negotiating connection to Country and place through collective storying - Wendy Somerville; Vahri McKenzie; Lisa Fuller; Naomi Joy Godden; Ashley Harrison; Renae Isaacs-Guthridge; Bethaney Turner (Australian Journal of Environmental Education)
Within this paper we explore the process and outcomes of a year-long exchange that investigates how active learning can emerge through collective place-based storying. Beginning with Country as our guide, we shared, responded, yarned, listened and revisited one another’s contributions. Using the “threads” of an extended email exchange and online yarning sessions, we wove together this collaborative work to present findings generated from the creative practice of storying and sharing knowledge. This work required ongoing openness to vulnerability; we resisted the urge to remain silent and risked being wrong. Our responses, and the writing styles reflecting them, incorporate both academic and creative approaches. As we negotiated connection to Country and place through collective storying, six key themes emerged: Country and personal sites of significance, honouring children and childhood, relationality, the significance of sensory engagement, the significance of vulnerability, and acknowledging Earth violence. This collaborative paper explores a practical approach, grounded in kindness, to negotiating connections to Country and place. We reflect on how we carefully nurtured the conditions that enabled the work to occur, sharing our experiences to help guide others navigating their own collective research practices.